Relating Independent Components to Free-Vibration Modal Responses - S.I. McNeill; D.C. Zimmerman (Shock and Vibration)
In recent literature, attempts have been made to apply Independent Component Analysis (ICA) techniques to the modal identification problem. Paramount to this task is establishing a relationship between the source components realized using the suggested ICA technique and modal responses. In this paper, the relationship between independent components and free-vibration modal responses is discussed. Theoretical arguments are presented for responses of undamped systems and arguments are extended to damped responses.